Therapeutic E cacy of Nyctanthes arbor-tristis Flowers to Inhibit Proliferation of Acute and Chronic Primary Human Leukemia Cells, with Adipocyte Di erentiation and in Silico Analysis of Interactions between Survivin Protein and Selected Secondary Metabolites - Heendeniya, S. N; Keerthirathna, L. R; Manawadu, C. K; Dissanayake, I. H; Ali, R; Mashhour, A; Alzahrani, H; Godakumbura, P; Boudjelal, M; Peiris, D. C. (Biomolecules, 2020)
Although the antidiabetic e cacy of Nyctanthes arbor-tristis ﬂowers has been reported, antiproliferative and anti-obesity activities are yet to be explored. We examined the anti-obesity and antiproliferative potentials of di erent fractions (hexane, chloroform, ethyl acetate, methanol) of N. abor-tristis ﬂower extract for the ﬁrst time using 3T3-L1 cells, primary peripheral blood mononuclear cells (PBMC) isolated from healthy and adult acute myeloid (AML) and chronic lymphocytic leukemia (CLL) patients, recombinant Jurkat T cells, and MCF7 cell lines. The in vitro hypoglycemic activity was evaluated using the inhibition of -amylase enzyme and glucose uptake by yeast cells. The percentage glucose uptake and -amylase inhibitory activity increased in a dose-dependent manner in the crude and the tested fractions (hexane and ethyl acetate). Inhibition of the 3T3-L1 cells’ di erentiation was observed in the ethyl acetate and chloroform fractions, followed by the hexane fraction. Antiproliferative analyses revealed that Nyctanthes exerted a high speciﬁc activity against anti-AML and anti-CLL PBMC cells, especially by the hexane and ethyl acetate fractions. The gas chromatography/mass spectrometry analysis indicated the presence of 1-heptacosanol (hexane fraction), 1-octadecene (hexane and chloroform fractions), and other organic compounds. Molecular docking demonstrated that phenol,2,5-bis(1,1-dimethylethyl) and 4-hydroxypyridine 1-oxide compounds showed speciﬁcity toward survivin protein, indicating the feasibility of N. abor-tristis in developing new drug leads against leukemia.
Keywords: Nyctanthes abor-tristis; human breast carcinoma; primary peripheral blood mononuclear cells; acute myeloid leukemia; chronic lymphocytic leukemia; obesity; hypoglycemia; molecular docking; survivin protein; gas chromatography/mass spectrometry